2015
DOI: 10.1088/1742-6596/626/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and separability in the noncommutative phase-space scenario

Abstract: Quantumness and separability criteria for continuous variable systems are discussed for the case of a noncommutative (NC) phase-space. In particular, the quantum nature and the entanglement configuration of NC two-mode Gaussian states are examined. Two families of covariance matrices describing standard quantum mechanics (QM) separable states are deformed into a NC QM configuration and then investigated through the positive partial transpose criterium for identifying quantum entanglement. It is shown that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…These results are in agreement with reference [30] in which it was shown that nonclassicality and entanglement are enhanced by increasing the noncommutativity of the underlying space (an alternate way of introducing minimal length similar to the GUP). Similarly, in ref [31], it is shown that the entanglement of Gaussian states can be induced by a noncommutative phase space scenario.…”
Section: Discussionmentioning
confidence: 77%
“…These results are in agreement with reference [30] in which it was shown that nonclassicality and entanglement are enhanced by increasing the noncommutativity of the underlying space (an alternate way of introducing minimal length similar to the GUP). Similarly, in ref [31], it is shown that the entanglement of Gaussian states can be induced by a noncommutative phase space scenario.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, with the new development of quantum information theory, the notion of non-commutativity of the space has been introduced to a multipartite system, to explore its effects on the quantum correlations between the subsystems. In this idea, Bernardini et al [11] studied the effects of two-dimensional position-space of non-commutativity on a bipartite entanglement and separability in the non-commutative phase space, using the positive partial transpose criterion. They observed that the entanglement of Gaussian states may be exclusively induced by switching on the non-commutative deformation.…”
Section: Introductionmentioning
confidence: 99%
“…As we converge to the point r = 1, we see that it vanishes which is exactly what we prescribe as the separability criterion, but away from the point r = 1, where the degree of anisotropy is non-trivial, the entanglement increases rapidly. It is clear from (35) that the measure of the entanglement is symmetric to the interchange of the oscillators.…”
Section: Entanglement For the Anisotropic Oscillator In Nc Spacementioning
confidence: 99%
“…Previously in the literature, separability criterion of oscillator systems has been discussed in terms of the covariance matrix [35]. However in this paper, we take a step ahead and provide a quantitative measure for such entanglement as well as analyze Simon's separability condition for our system.…”
Section: Introductionmentioning
confidence: 99%